INDUKSI KALUS TANAMAN KAKAO (THEOBROMA CACAO L.) PADA MEDIA MS DENGAN PENAMBAHAN 2,4-D, BAP DAN AIR KELAPA - Ariati, Sri Niken; Waeniati, Waeniati; Muslimin, Muslimin; Suwastika, I Nengah (Natural Science: Journal of Science and Technology, 2012)
Study on callus induction of cacao (Theobroma cacao L.) was conducted at the Tissue Culture laboratory, Forestry faculty, Tadulako University, Palu, during periode of January until April 2012. This research was aimed to obtain the best medium formulation for induction and growth of cacao callus. Calli was induced from embryo  on MS based medium containing of 2,4-D, BAP and coconut water. The intact plant as explant was taken from Local Farming. This experiment was arranged in completely randomized  design with 4 treatments and 3 replications. The treatments were : MS medium + 2 ppm 2,4-D + 15% coconut water (N1), MS medium + 2 ppm 2,4-D + 0,2 ppm BAP, 15% coconut water (N2), MS medium + 2 ppm 2,4-D + 0,2 ppm BAP (N3), and MS medium + 2 ppm 2,4-D (N4). Parameters observed in this study were the days appear of callus, percentage of explant producing callus (%), also observation on morphology and the cell of callus. The best medium for callus  induction was MS medium + 2 ppm 2,4-D + 15% coconut water (N1). This medium produces healthy-compac callus which active in cell proliferation, in 6 days after induction.